The Right Thing at the Right Time: Why Ostensive Naming Facilitates Word Learning - Axelsson, Emma L.; Churchley, Kirsten; Horst, Jessica S. (Frontiers in Psychology, 2012)
The current study examines how focusing children’s attention during referent selection improves their ability to retain novel names. Previous research suggests that young children can only retain novel names presented via referent selection if ostensive naming is provided and that ostensive naming works by increasing children’s attention to the target and decreasing their attention to the competitor objects (Horst & Samuelson, 2008). This explanation of the function of ostensive naming was tested by presenting 24-month-old children with a referent selection task where their attention was drawn to the target either by illuminating the target, covering the competitors or both. A control group was given a pragmatic cue (pointing). Children only demonstrated retention if the target object was illuminated, suggesting that drawing children’s attention to the target object and away from the present competitors is critical for word learning via referent selection to occur. In contrast, children given pragmatic-cue support did not perform better than chance. Children performed best when both cues (illumination and covering) were used.